2008
DOI: 10.1007/s11664-008-0584-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Epitaxial Graphene Formation on SiC(0001)

Abstract: The formation of epitaxial graphene on SiC(0001) surfaces is studied using atomic force microscopy, Auger electron spectroscopy, electron diffraction, Raman spectroscopy, and electrical measurements. Starting from hydrogenannealed surfaces, graphene formation by vacuum annealing is observed to begin at about 1150°C, with the overall step-terrace arrangement of the surface being preserved but with significant roughness (pit formation) on the terraces. At higher temperatures near 1250°C, the step morphology chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 21 publications
11
52
0
Order By: Relevance
“…Pits are formed during the initial stage, associated with the formation of the 6√3×6√3-R30° surface reconstruction. 12,13,14,15 This reconstruction persists as the graphene forms, located at the interface between the graphene and the SiC and thus acting as a template for the graphene formation. LEEM provides a direct measure of the thickness of a graphene film at each point on the surface, 16 revealing oscillations in the reflectivity of electrons which are dependent on the film thickness and beam energy.…”
Section: Introductionmentioning
confidence: 98%
“…Pits are formed during the initial stage, associated with the formation of the 6√3×6√3-R30° surface reconstruction. 12,13,14,15 This reconstruction persists as the graphene forms, located at the interface between the graphene and the SiC and thus acting as a template for the graphene formation. LEEM provides a direct measure of the thickness of a graphene film at each point on the surface, 16 revealing oscillations in the reflectivity of electrons which are dependent on the film thickness and beam energy.…”
Section: Introductionmentioning
confidence: 98%
“…1(b)) from which a thickness of 3 6 1 ML was estimated based on the height ratio of the C KLL and Si LMM peaks; the calibration curve used is produced from the determination of C:Si sensitivity factors. 24,25 This was supported by Raman spectroscopy measurements of the width of the 2D peak found at 2750 cm À1 . Raman measurements also indicated that the graphene is of a high quality due to the small size of the D peak observed at 1380 cm À1 (not shown).…”
mentioning
confidence: 64%
“…For our epitaxial graphene FETs with moderate mobilities compared to exfoliated graphene [2,22], we expect many mechanisms to coexist, among which the surface phonons and morphological disorder dominate, due to the use of the high-k dielectric [20] and the rough surface morphology (see AFM images in Refs. [9] and [23]), respectively. For the morphological disorder, it is reasonable to assume the mean free path v F τ as determined by surface roughness and average graphene domain size, thus independent of the carrier density.…”
Section: Discussionmentioning
confidence: 99%
“…Our epitaxial synthesis and thickness estimate of graphene on the Si-face have been described elsewhere [9]. The average thicknesses of both Si-face samples were estimated to be ~ 2 ML by Auger electron spectroscopy (AES) (this thickness does not include the C-rich "buffer layer" at the SiC/graphene interface [9]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation